The effect of customer satisfaction on customer loyalty in the motor industry - Lim, Ka Bian; Haque, A. K. M. Ahasanul; Wok, Saodah; Tarofder, Arun Kumar (Universidad del Zulia, 2019)
This study aims to determine the effects of three exogenous variables, namely, service quality, price fairness and Shari’ah compliance on customer loyalty through customer satisfaction as the mediator. Applying the theory of customer satisfaction, a structural equation model was developed and tested on 322 motor Takaful participants from the Klang Valley, Malaysia. The findings suggest that customer satisfaction partially mediates the effects of Shari’ah compliance and price fairness on customer loyalty. In conclusion, participants of motor Takaful are not concerned about the service quality; they are mainly influenced by the price fairness and Shari’ah compliance of the products /services. ************************************************************************** El objetivo de este estudio es determinar los efectos de tres variables exógenas, a saber, la calidad del servicio, la imparcialidad de los precios y el cumplimiento de Shari’ah sobre la fidelidad del cliente a través de la satisfacción del cliente como mediador. Aplicando la teoría de la satisfacción del cliente, se desarrolló un modelo de ecuación estructural y se probó en 322 participantes de Takaful motor de Klang Valley, Malasia. Los hallazgos sugieren que la satisfacción del cliente media parcialmente los efectos del cumplimiento de Shari’ah y la imparcialidad de los precios en la lealtad del cliente. En conclusión, los participantes de motor Takaful no están preocupados por la calidad del servicio, están principalmente influenciados por la imparcialidad de los precios y el cumplimiento de Shari’ah de los productos / servicios.